Anticonvulsants and Chromatin-Genes Expression: A Systems Biology Investigation - Kowalski, Thayne Woycinck; Gomes, Julia do Amaral; Feira, Mariléa Furtado; Dupont, Ágata de Vargas; Recamonde-Mendoza, Mariana; Vianna, Fernanda Sales Luiz (Frontiers in Neuroscience, 2020)
Embryofetal development is a critical process that needs a strict epigenetic control; however, perturbations in this balance might lead to the occurrence of congenital anomalies. It is known the anticonvulsants potentially affect epigenetics-related genes; however, it is not comprehended whether this unbalance could explain the anticonvulsants-induced fetal syndromes. In the present study, we aimed to evaluate the expression of epigenetics-related genes in valproic acid, carbamazepine, or phenytoin exposure. We selected these three anticonvulsants exposure assays, which used murine or human embryonic stem-cells and were publicly available in genomic databases. We performed a differential gene expression (DGE) and weighted gene co-expression network analysis (WGCNA), focusing on epigenetics-related genes. Few epigenetics genes were differentially expressed in the anticonvulsants’ exposure, however the WGCNA strategy demonstrated a high enrichment of chromatin remodeling genes, for the three drugs. We also identified an association of 46 genes related to Fetal Valproate Syndrome, containing SMARCA2 and SMARCA4, and nine genes to Fetal Hydantoin Syndrome, including PAX6, NEUROD1, and TSHZ1. The evaluation of stem-cells under drug exposure can bring many insights to understand the drug-induced damage to the embryofetal development. The candidate genes here presented are potential biomarkers that could help in future strategies for the prevention of congenital anomalies.